A Newly Identified Fragment in the Handwriting of William Tyndale. Issue 1 (3rd July 2014) - Cooper, W. R.
Abstract : During an otherwise fruitless search of the British Library's Foxe papers, a document surfaced that has proved to be in the handwriting of William Tyndale. The document is today but a fragment and is a reworking of an old Lollard tract on why the Bible should be translated into English. Tyndale's activities in modernizing old Lollard tracts for his Tudor readers have always been recognized, yet this tract has never been counted amongst his works. The full and improved text of the tract was printed in 1530 by 'Hans Luft' along with other works by Tyndale (including his Pentateuch). Apart from the Yilvorde letter Tyndale wrote from his cell before he was burned, this is the only other known paper written in his hand. The full text of the fragment and its printed version are reproduced in this article as appendices.